Feline Distal Tibial Physeal Fracture Repair Using a Modified Cross-Pin Technique with Four Pins - Miraldo, Diogo; Salmelin, Bettina; Yeadon, Russell (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this article was to report the surgical technique and clinical outcome of a modified cross-pin technique for the treatment of distal tibial physeal fractures in cats without postoperative external coaptation.Study Design This study was a retrospective clinical study.Animals A total of 9 cats were presented with fracture of the distal tibial physis.Materials and Methods Medical records from July 2014 to September 2018 were reviewed. In all cases, a second medial and a craniolateral Kirschner wires were added to the traditional cross-pin technique. Information reviewed included orthogonal radiographs pre- and post-surgery and at subsequent re-examinations, subjective assessment of lameness and passive range of motion, veterinary clinical assessment and completion of a functional questionnaire (feline musculoskeletal pain index) at the time of writing this report. Eight owners completed the questionnaire. The mean questionnaire follow-up time was 12.7 months.Results Uncomplicated fracture healing occurred in all patients. Two patients required implant removal due to Kirschner wire migration and protrusion through the skin at 5 and 12 months post-surgery. No other complications were noticed. Eight patients had an excellent outcome, and one patient had a good outcome.Conclusion Distal tibial physeal fractures in cats can be treated successfully with the use of a modified cross-pin technique and without the use of external coaptation. Prognosis should be considered favourable for this type of fracture.
Keywords: fracture repair; physeal fracture; feline; tibia; physis